Prevention of the hand-arm vibration syndrome. - Saito, Kazuo (Scandinavian Journal of Work, Environment & Health, 1987)
In order to determine the prevalence of the hand-arm vibration syndrome before preventive countermeasures were taken, a special health examination was carried out among 417 national forestry workers operating chain saws in the northern area of Hokkaido, Japan. Thirty-two chain-saw workers (7.7%) were diagnosed as exhibiting the vibration syndrome. The highest prevalence rates were 15.8% among the workers who had operated the saws for 11 to 15 years and 20.3% for workers in their 50s. Improved work conditions for chain-saw workers have increasingly prevented the vibration syndrome in the state forests of Japan since 1978. The present report covered the six years since 1978, and evaluated the effects of these improved work conditions on chain-saw workers from data on the recovery rates of skin temperature and the vibration sense threshold after a cold provocation test. As a result, recovery rates of skin temperature and the vibration sense thresholds at the fifth and tenth minutes after the immersion of the hands in cold water were significantly better than those six years earlier. It is suggested that adequate restrictions on the operating time of the chain saw and on the age of workers can completely prevent the vibration syndrome even if the total operating time is appreciably lengthened.